Commercial Production of Ornamental Tropical Foliage Plants: Micropropagation - Jianjun Chen; Richard J. Henny (EDIS)
Florida nursery operators need to understand plant propagation principles and techniques so they can grow enough plants for sale. Micropropagation is a way to culture plant tissue to rapidly propagate a large number of plants. This 4-page fact sheet presents an overview of micropropagation to help growers evaluate it as a propagation technique for their own nursery operations. Written by J. Chen and R. J. Henny, and published by the UF Department of Environmental Horticulture, May 2015. (Photo: J. Chen, UF/IFAS)